Functional Thyroid Organoids—Powerful Stem Cell-Derived Models in Basic and Translational Research - Meghna Parakkal Shankar; Alessandra Boggian; Daniela Aparicio-Quiñonez; Sami Djerbib; Eduardo Rios-Morris; Sabine Costagliola; Mírian Romitti (Biomolecules)
Thyroid organoids, three-dimensional in vitro models derived from stem cells, have emerged as a powerful tool for studying thyroid development, function, and disease mechanisms. These organoids recapitulate the key aspects of the thyroid gland, including the follicular structure, hormone production, and response to stimuli such as to the thyroid-stimulating hormone (TSH). Recent advances in thyroid organoid technology have established the basis for the modeling of development and thyroid diseases, including congenital hypothyroidism (CH), autoimmune conditions like Graves’ disease and Hashimoto’s thyroiditis, and other thyroid-related disorders. By utilizing pluripotent stem cells (PSCs) and adult tissue, researchers have generated organoid models suitable for dissecting the mechanisms associated with thyroid development while mimicking the genetic, functional, and inflammatory characteristics of thyroid diseases. Additionally, thyroid organoids offer the potential for personalized medicine by providing a platform to test therapies in a more clinically relevant context. This review highlights the recent progress in thyroid organoid generation, discusses their applications in dissecting the thyroid development mechanisms and disease modeling, and explores their potential for advancing our understanding of the thyroid physiology and pathology. Furthermore, we address the challenges and future directions in the optimization and use of thyroid organoids in translational research.